Secondary prevention in patients with coronary heart diseases: what factors are associated with health status in usual primary care? - Ose, Dominik; Rochon, Justine; Campbell, Stephen; Wensing, Michel; Uhlmann, Lorenz; Freund, Tobias; Szecsenyi, Joachim; Ludt, Sabine (PLOS ONE, 2012)
For patients with coronary heart diseases a substantial part of secondary prevention is delivered in primary care. Along with the growing importance of prevention, health-related quality of life (HRQoL) is an indicator of patient-centered care that has gained increased attention. Different approaches for reorganization in primary care have been associated with improvements in HRQoL. However, these are often results of complex interventions. Evidence on aspects concerning usual primary care that actually have an impact on HRQoL remains scarce. Therefore, this observational study aimed to identify factors which are associated with HRQoL in usual primary care at practice and patient-level.
Gesehen am 05.11.2018